Effect of pulsed electromagnetic fields (PEMFs) on condrogenic phenotype maintenance of MSCs in presence of pro-inflammatory cytochines: preliminary results - Palumbo, Carla; Ferretti, Marzia; Bertoni, Laura; Cavani, Francesco; Benincasa, Marta; Sena, Paola; Sacchetti, Gian Luigi; Setti, Stefania; Cadossi, Ruggero (Italian Journal of Anatomy and Embryology, 2011)
The aim of the study was to evaluate in vitro the effects of PEMFs on maintenance over time of chondrocyte phenotype of conditioned Mesenchimal Stem Cells (MSCs), in presence of pro-inflammatory cytokines (IL-ß1). MSCs, taken from bone marrow, were pellet-cultured in medium conditioning towards the chondrogenic lineage. Two targets were pursued: the first was to standardize the method to obtain chondrocyte pellets in terms of type/amount of withdrawal, time/degree of differentiation and amount of extracellular matrix production; the second was to extend over time chondrocyte differentiation, checking the phenotype maintenance, after adding pro-inflammatory IL-ß1 cytokine in culture medium with/without the application of PEMFs (device provided by IGEA-Carpi). The pellets obtained were coltured for different times (21, 28, 34 days), verifying the presence of type-II collagen (as index of chondrocyte differentiation) both by means of TEM analysis and immunoreaction. The best differentiation was obtained after 28 days of culture; in such pellets the studies were performed in triplicate for 15 days, identifying four experimental conditions: 1) without IL-ß1 and PEMFs; 2) with IL-ß1, without PEMFs; 3) without IL-ß1 and with PEMFs; 4) with IL-ß1 and PEMFs. The parameters of applied PEMFs were 1.7mT and 75Hz, and the time of application was 4 hours/day. Medium was changed every 3-4 days and stored for the evaluations of PGE2 (indicative of inflammation) and proteoglycans (indicative of chondrogenic differentiation). At the end of the experiment, each pellet was fixed with paraformaldehyde 4% and embedded in paraffin; sections (5 µm thick) were obtained and stained with Toluidin Blue in order to evaluate metachromasia. The results show that: 1) only the pellets treated with IL-ß1 without PEMFs did not show metachromasia, indicanting a chondrocyte de-differentiation towards fibroblastic phenotype; 2) only in pellets treated with IL-ß1 and with PEMF application, after about 12 days of treatment the amount of PGE2 in medium decreases (31%), indicating the anti-inflammatory effect of PEMFs, while the proteoglycan production slightly increases (2%). In conclusion, pulsed electromagnetic fields could be proposed in preventing chondrocyte de-differentiation due to inflammation induced by IL-ß1; this with the final aim to integrate regenerative medicine techniques to apply in the healing of joint cartilage lesions with bio-physic energy devices, useful to obtain a stable-in-time recovery of physiologic function of articular surfaces that suffered a severe injury.